Implementasi Peraturan Gubernur Sumatera Utara Nomor 29 Tahun 2020 Dalam Rangka Meningkatkan Pelaksanaan Tugas Pegawai Di Biro Admnistrasi Pimpinan Sekretariat Daerah Provinsi Sumatera Utara - Fadila, Cindy; Angelia, Nina; Kurniaty, Evi Yunita (Universitas Medan Area, 2024)
The Leadership Administration Bureau is a government organization located in the North Sumatra Governor's office which has the main task of serving the leadership, starting from preparing leadership materials, preparing leadership activity materials and reporting. However, in its implementation there are still employees who have not fully carried out their duties properly due to a fairly large workload imposed on them so that in carrying out their duties they lack discipline and lack of work motivation and also lack of competence and trainings made. This study aims to determine the implementation of North Sumatra Governor Regulation No. 29 of 2020 in order to improve the implementation of employee duties in the Leadership Administration Bureau and what are the inhibiting factors in its implementation. The theory used in this study is theory of Edwards III, particulary Communication, Resources, Disposition, and Bureaucratic Structure. The use of this studies approach is a qualitative method the usage of remark statistics series techniques, in-depth interviews, and documentation. This investigation revealed that the was not yet fully implemented due to the still obstacles, one of which is that some of the human resources are not competent, and also the lack of training and socialization about work in the Leadership Administration Bureau makes them lacking in obtaining training while for communication, disposition, and bureaucratic structure have been implemented quite well and small problems they are able to overcome.